2011
DOI: 10.1093/gerona/glr167
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet Supplemented With Coenzyme Q10 Modifies the Expression of Proinflammatory and Endoplasmic Reticulum Stress–Related Genes in Elderly Men and Women

Abstract: We have investigated whether the quality of dietary fat and supplementation with coenzyme Q(10) (CoQ) modifies expression of genes related with inflammatory response and endoplasmic reticulum stress in elderly persons. Twenty participants received three diets for 4 weeks each: Mediterranean diet + CoQ (Med + CoQ), Mediterranean diet (Med), and saturated fatty acid-rich diet (SFA). After 12-hour fast, volunteers consumed a breakfast with a fat composition similar to that consumed in each of the diets. Med and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 47 publications
2
55
1
1
Order By: Relevance
“…In addition, in another study was seen that CoQ10 administration at a dosage of 20 mg/kg increased insulin sensitivity and had antidiabetic properties via increasing activity of phosphatidylinositol kinase (PI3K) in rats fed a high-fat, high-fructose diet [7]. Mediterranean diet with CoQ10 also modified gene expression of pro-inflammatory markers among elderly men and women for four weeks [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in another study was seen that CoQ10 administration at a dosage of 20 mg/kg increased insulin sensitivity and had antidiabetic properties via increasing activity of phosphatidylinositol kinase (PI3K) in rats fed a high-fat, high-fructose diet [7]. Mediterranean diet with CoQ10 also modified gene expression of pro-inflammatory markers among elderly men and women for four weeks [8].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a diet rich in vegetables, fruits, fish, and unsaturated fats is associated with anti-inflammatory gene profile, while the opposite has been found for Western diet consisting of saturated fats, sugars, and refined food products (58). Similar changes have been observed in older adults after just one Mediterranean diet meal (59) or in healthy adults after consuming 250 ml of red wine (60) or 50 ml of olive oil (61). However, in spite of this literature, only two of the studies we reviewed tested if the MBIs had any influence on lifestyle (e.g., sleep, diet, and exercise) that may have explained gene expression changes.…”
Section: Discussionsupporting
confidence: 61%
“…In a similar study, consumption of Mediterranean diet supplemented with CoQ10 for 4 weeks in elderly subjects produced a lower postprandial MMP-9 and IL-1β gene expression, compared with control diets. 41 Inui et al showed that UVBinduced MMP-1 production of normal keratinocyte decreased in the presence of CoQ10. 33 In another study, Bahar et al reported that incubation of CoQ10 reduced MMP-2 activity in MCF-7 cell line as a breast cancer cellular model at a dose proportionate manner.…”
Section: Discussionmentioning
confidence: 99%